The Validation of the Sample6 DETECTTM HT/L for AOAC Research Institute. (23rd November 2019) - Banerjee, Kakolie; Pierson, Brittney; Hu, Chuxuan; Carrier, Elijah; Malsick, Lauren; Tarasova, Yekaterina; Daudenarde, Sophie; Brownell, Daniel; Koeris, Michael; Klass, Nicole; Bird, Patrick; Benzinger, M Joseph; et al.
Abstract: Background : Listeria spp. are an important foodborne human pathogen because of their ability to cause disease and high mortality in individuals, particularly pregnant women, neonates, the elderly, immunocompromised individuals, and children. The Sample6 DETECT TM HT/L Kit is a semi-automated qualitative pathogen detection system designed to detect Listeria spp. ( L. monocytogenes, L. innocua, L. ivanovii, L. seeligeri, L. welshimeri, and L. marthii ) in environmental samples using the Sample6 BioIllumination TM technology. Objective : The study was done to evaluate the Sample6 DETECT HT/L Kit. The assay was evaluated for inclusivity, exclusivity, robustness, product consistency, and stability, and a matrix study of one environmental surface. Methods : The performance of the Sample6 DETECT HT/L was compared with U.S. Food and Drug Administration reference culture method for Listeria using an unpaired study design. Results : The Sample6 DETECT HT/L assay correctly identified all 50 inclusivity isolates and correctly excluded all 30 nontarget strains evaluated. The assay was not affected by minor variations in incubation temperature and time, or sample volume. Results across three production lots spanning the shelf life of the assay were consistent. In the matrix study, the Sample6 DETECT HT/L for Listeria correctly identified each test portion for the presence or absence of Listeria, and there were no statistically significant differences between candidate and reference method results. Conclusions : The data collected in this study demonstrate that the Sample6 DETECT HT/L assay is a reliable method for the detection of Listeria spp. on stainless-steel environmental surfaces after 22 h of enrichment.